Study the Effect of Guide Sign Position on Traffic Behavior at Exit Freeway Weaving Areas by Developing Computer Simulation Program (FWASIM) (Iraqi Journal of Civil Engineering, 2008)
Traffic control devices notify road users of regulations and provide warning and guidance needed for safe, uniform, and efficient operation of all elements of the traffic stream. Traffic control devices have been a part of the roadway system. Researches have evaluated various aspects of the design, operation, placement, and maintenance of traffic control devices. The purpose of this research is to develop a simulation model in order to evaluate the effect of overhead sign position on the traffic performance at exit of freeway weaving area. To achieve that subroutine was developed and added to FWASIM program to compute the sign position and compare it with the driver sight distance. Following that a proposed example represents an exit weaving area was examined with different traffic flow configuration (different percentages of link flow and on-ramp flow) with respect to no sign installed and other three sign positions. Results indicate that the average traffic speed is underestimated when there is no sign installed, while no significant effect is shown when the sign position is changed within the driver sight distance. In conclusion Guide signing is a critical element in the effective, efficient and safe operation of motorways and expressways. Signing issues must, therefore, be fully considered at the feasibility stage of any project.